2006
DOI: 10.3122/jabfm.19.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Does Gel Affect Cytology or Comfort in the Screening Papanicolaou Smear?

Abstract: Purpose: Current medical training recommends obtaining cervical cytological specimens without the use of lubricating gel. The purpose of this study was to determine whether water-soluble lubricant gel affects cytologic outcomes in the screening Papanicolaou smear and patient comfort during vaginal speculum examination.Methods: The study was a randomized controlled trial performed at David Grant US Air Force Medical Center (Travis Air Force Base, CA). Participants were female patients at least 18 years old pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 7 publications
4
24
3
1
Order By: Relevance
“…Because our study group included a relatively high number of postmenopausal women, the overall significant effect of gel application can be explained by the effectiveness in this subgroup. The reason for the nonsignificant results of Gilson et al 13 in discomfort rating regarding lubricant gel use may be the low number of postmenopausal women in their study (the group included 10 postmenopausal and 60 premenopausal women).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Because our study group included a relatively high number of postmenopausal women, the overall significant effect of gel application can be explained by the effectiveness in this subgroup. The reason for the nonsignificant results of Gilson et al 13 in discomfort rating regarding lubricant gel use may be the low number of postmenopausal women in their study (the group included 10 postmenopausal and 60 premenopausal women).…”
Section: Discussioncontrasting
confidence: 39%
“…In the study by Gilson et al, 13 a numeric pain scale was used to investigate the discomfort level of patients. They used a dry speculum to obtain Pa- panicolaou test specimens in 70 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, it has also been shown that lubrication of the external surfaces of the speculum blades with a small amount of gel does not significantly reduce patient discomfort during speculum examination. 8 Although increasing the amount of gel lubricant should reduce the discomfort associated with speculum insertion, data are lacking concerning the effects on the Pap smear from contamination of the cervix by greater than normal amounts of gel lubricant. The aim of this study was to explore those effects by determining the proportion of unsatisfactory Pap smears and the discordance in diagnoses between gel-contaminated smears and uncontaminated smears from the same patients.…”
Section: Lubricating Gel Contamination Of the Cervix Can Adversely Afmentioning
confidence: 99%
“…They found that it had no negative effect on the cytological evaluation of cervicovaginal smear, and that stated that it might be used for the comfort of the patient if she chooses (9). Moreover, it was proposed that bimanual examination could be carried out by using gel if the cervix was not visible with a speculum (9).…”
Section: Discussionmentioning
confidence: 99%